A nested framework for transparency in Public Private Partnerships: Case studies in highway development projects in India. (July 2016) - Mukhopadhyay, Chandrima
Graphical abstract: Highlights: Limited transparency in partnership formation restricts the scope of public scrutiny. Double stage partnership at regional level is debatable in terms of accountability. Affected communities experience non-transparent and unfair land acquisition process. The existing land acquisition process fails to create culture of openness. Independent engineers as watchdog of accountability has limited power. Abstract: Public Private Partnership (PPP) offers an innovative framework of accountability in comparison to traditional public sector procurement model. Transparency is one of the four components of the framework. Whereas theoretically PPP calls for restricted transparency, policy makers have recently raised their voices for improved transparency of public infrastructure delivery process throughout the project cycle. But the question arises what transparency is and what does it do? This research offers a framework of transparency to understand the wider concept both in depth and breadth, drawing on the literature of decision-making in mega projects, PPP and understanding of transparency under various theoretical paradigms. Three highway projects from the eastern part of India are examined and conclusions are also based on case study findings, considering the extent they can be framed under various theoretical paradigms under review.Hood and Heald's (2006) framework on categories of transparency based on time and direction of disclosure of information is also used to suggest how altering time and direction of disclosure would have better served the purposes of transparency.